THE IMPLEMENTATION OF SINGING TO IMPROVE COUNTING ABILITY FOR YOUNG LEARNERS - Anita Roslina Simanjuntak (Magister Scientiae, 2020)
The purpose of this study is to describe the process and learning outcomes through singing methods that can improve children's counting skills. The subjects of this action research were 13 children. This research method is an action research that refers to the Kemmis Mc Taggart action research model which consists of the stages of planning, action, and observation, and reflection. This research consisted of 2 cycles, where each cycle consisted of 8 meetings. Data analysis techniques used in this study are quantitative and qualitative data analysis techniques. Quantitative data analysis with descriptive statistics that compares the results obtained from the pre cycle, the first cycle, to the second cycle. Qualitative data analysis by analyzing data from the results of field notes, interview notes, and documentation notes with the stages of data reduction, data display, and conclusions. The results of this study indicate an increase in the ability to counting through singing in which the average value in the pre cycle of 2.76 increased in the first cycle to be 3.38, and in the second cycle to be 5.07.